Association between Participation in Counseling and Retention in a Buprenorphine-Assisted Treatment Program for People Experiencing Homelessness with Opioid Use Disorder - Amanda R. W. Berry (MDPI AG, 2021)
The opioid epidemic is a public health crisis that disproportionately affects our unsheltered neighbors. Because medication-assisted treatment (MAT) is effective for preventing deaths from drug overdose and retention is associated with better health outcomes, there is a clear need for more research on factors impacting retention in care. This retrospective cohort analysis examines the relationship between attendance in counseling and retention on buprenorphine for three or more months for individuals experiencing homelessness being treated at a Federally Qualified Health Center (FQHC) and Public Health Service Act §330(h) Health Care for the Homeless Program grantee in San Diego County, California. The cohort included 306 adults experiencing homelessness who had at least one prescription for buprenorphine and participated in a MAT program between 2017 and 2019. The sample included 64.4% men, almost exclusively white, and 35% lived in a place not meant for human habitation. Of the sample, 97 patients were retained at 3 months and 209 were not. Results from a logistic regression model showed that counseling appointments were positively associated with retention at three months (OR = 1.57, p < 0.001). Findings from this study inform future MAT program design components for people experiencing homelessness.